Comparison between two methods for the determination of root canal length in primary teeth (Journal of Hama University, 2022)
Aims and Objectives:The purpose of this in vitro study was to compare the root canal length determination by Electronic apex locator (EAL) and conventional radiography, and then compare them with the actual measurements obtained by direct visualization.Materials and Methods: One hundred rooted primary teeth extracted due to extensive caries, trauma, serial extraction or unwillingness of the parent to save the teeth were selected. The teeth were numbered and root canal length was determined using the visual, electronic and the radiographic methods. The actual, electronic and the radiographic measurements were recorded. Conclusion: Using a criterion of ± 0.5 mm, the accuracy of the electronic apex locator was high and proved to be more accurate in determining the root canal length than the radiographic method.
Keywords: Electronic apex locator, primary teeth, root canal length determination